PECULIARITIES OF BIOGENIC SUBSTANCES REGIME FORMATION ON THE WESTERN SGELF OF THE MIDDLE CASPIY - G. A. Akhmedova (Юг России: экология, развитие, 2014)
Aim. Investgation of conditions of hydrochemical regime formation in the north-westen part of the Middle Caspiy.Methods. Literature date on biogenic flow of the Volga and the data of expeditionalhydrochemical observations over 1978-1987 (January, March, May, July, September, October) in the regions of Daghestan coast of the Middle Caspiy–dopatin, coastal waters of the Terek and Sulak, Makhachkala, Caspiysk, Izberbash, Derbent, coastal waters of the Samur on the skylines of Ometers and at the bottom as for period with the largest number of continuous observation have been used for the analysis.Results. It was supposed in the paper that the content of of biogenic substances in the nerth Caspian waters depended not only upon coming with the Volga flow, but upon the other factors, regulating the modification in sea environment.Main conclusions. Knowledge of mechanism of water object functioning in the conditions of climate change andantropogenetic burden, understanding of the reaction of water object mechanism on these changes permits to plan agricultural activity in zones of its forecasting influence more rationally.